2005
DOI: 10.1057/palgrave.crr.1540233
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reputation and Crisis Management: The Threat and Manageability of Anti-corporatism

Abstract: Advances in technology and communication have rendered corporate reputations more vulnerable than ever to criticism and attack from anti-corporate pressure groups, which now have the capacity to reach a global audience and mobilize their protests at a multinational level. This paper will discuss the increasing value of corporate reputation as a source of differential advantage in the global marketplace, and the threats that exist to even the most reputable organizations. Based on this analysis, the paper will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 7 publications
2
61
0
2
Order By: Relevance
“…Schnietz and Epstein (2005) , for example, identify social responsibility as a key dimension of reputation; Tucker and Melewar (2005) see social responsibility as a critical element of reputation relevant to crisis management and Lindgreen and Swaen (2005) argue that issues relating to responsibility are embedded within the functional relationships that underpin business activities. They suggest, therefore, that there will be a signifi cant overlap between the reputation for these activities and the reputation for issues relating to responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Schnietz and Epstein (2005) , for example, identify social responsibility as a key dimension of reputation; Tucker and Melewar (2005) see social responsibility as a critical element of reputation relevant to crisis management and Lindgreen and Swaen (2005) argue that issues relating to responsibility are embedded within the functional relationships that underpin business activities. They suggest, therefore, that there will be a signifi cant overlap between the reputation for these activities and the reputation for issues relating to responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Grunwald, 2008: 74 ff. ;Standop 2006 ;Tucker and Melewar, 2005 ;De Matos and Veiga, 2004: 3 ;Dean, 2004 ;Cameron, 2004, 1998 ;Gutteling, 2001 ;Dawar and Pillutla, 2000 ;Tadelis, 1999 ;Coombs, 1998: 181 ;Dawar, 1998 ;Al-Najjar, 1995 ;Siomkos and Kurzbard, 1994 ;Siomkos and Shrivastava, 1993 ;Mowen, 1980 ). However, the determinants mentioned above have not yet been addressed in the framework of the underlying crises situations and with regard to reputation for quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although injuries caused by product defects can severely damage consumer confidence, notable recalls involving products from Coca-Cola and Mercedes Benz have demonstrated that consumer opinions on firm responsibility play a fundamental role in effective crisis management (Tucker and Melewar, 2005). Customers that believe suitable elimination processes were implemented are more likely to perceive a company as dependable and cooperative (Mishra, Heide, and Cort, 1998).…”
Section: Product Discontinuancementioning
confidence: 99%
“…However, studies have shown that while product demand may slightly weaken in reaction to negative product information (Govindaraj et. al 2004;Andrews, 2006), the extent of the associated fallback depends on consumer perceptions of candor, transparency, and problem severity (Dean, 2004;Tucker and Melewar, 2005;Standop, 2006;Grunwald, 2008;Polinksy and Shavell, 2010). Therefore, companies that take greater strides to provide consumers with comprehensive product information will stand in a better position to build consumer trust, leading to increased market share and profits.…”
Section: Product Offering Modificationmentioning
confidence: 99%